Applications of piezoelectric-based sensors, actuators, and energy harvesters - Mohammad Ali Mangi; Hassan Elahi; Ahsan Ali; Hamid Jabbar; Anas Bin Aqeel; Aasia Farrukh; Saira Bibi; Wael A. Altabey; Sallam A. Kouritem; Mohammad Noori (Sensors and Actuators Reports)
From the last few decades, piezoelectric materials have played an important role in the field of sensing and actuating. They have voltage-dependent actuation, which allows them to serve as energy harvesters and structural health monitoring of the system. This phenomenon makes piezoelectric sensors and actuators useful for monitoring and controlling various physical phenomena, such as vibration, shock, position, displacement, stress, strain load, and precision motion. In this review article, a comprehensive summary of the uses of piezoelectric sensors, actuators and energy harvesters is elaborated in detail. Moreover, the discussion on the different types of piezoelectric sensors, actuators and energy harvesters, their working principles, different configurations and their use in various industrial applications is carried out. Overall, this review article demonstrates the versatility and effectiveness of piezoelectric sensors and actuators in various industrial applications and provides valuable insights for researchers, engineers, and industry professionals.